State Responsibility and Food Safety Supervision in the Free Nutritious Meal Program: A Constitutional and Health Law Analysis - Sugiarti, Taty; Arifin, Firdaus; Maarif, Ihsanul (As-Siyasi: Journal of Constitutional Law, 2026)
Food safety is a critical component of public health governance, particularly in large-scale food programs where inadequate hygiene and sanitation can increase the risk of foodborne disease. In Indonesia, the Free Nutritious Meal Program relies on catering services whose compliance with food hygiene standards is essential to protect beneficiaries, especially school-aged children. This study examines the legal and institutional supervision of catering hygiene and sanitation within the program from a constitutional and health law perspective. Using normative juridical research supported by a socio-legal approach, the study operationally analyzes statutory regulations, policy frameworks, and institutional practices through library research and document analysis of national laws, technical regulations, and international food safety standards. Qualitative interpretative analysis was employed to evaluate regulatory effectiveness, supervisory mechanisms, and governance challenges. The findings reveal that Indonesia possesses a relatively comprehensive food safety regulatory framework; however, the effectiveness of supervision remains constrained by limited institutional capacity, fragmented inter-agency coordination, and inconsistent compliance among food service providers. This study identifies a persistent gap between regulatory norms and practical enforcement, emphasizing the need for integrated regulatory enforcement, risk-based supervision, and stronger institutional collaboration. The research contributes to health law scholarship by strengthening the conceptual understanding of food safety governance in public food programs. Limitations include reliance on normative and policy analyses without direct field observation, suggesting the need for future empirical studies of implementation practices at local operational levels